Heterotopic Ossification after Arthroscopic Elbow Release. Issue 5 (16th November 2020) - Yang, Chao‐qun; Hu, Jun‐sheng; Xu, Jian‐guang; Lu, Jiu‐zhou
Abstract : Objectives: To evaluate the incidence and risk factors of heterotopic ossification (HO) after arthroscopic elbow release. Methods: The present study included 101 elbows, with arthroscopic release performed on 98 patients over the 5‐year period from November 2011 to December 2015. Patients were divided into three groups: group 1, with elbow arthritis, including 46 elbows in 43 patients; group 2, with posttraumatic extrinsic elbow stiffness (without intraarticular adhesion), including 23 elbows in 23 patients; and group 3, with intrinsic contractures (with intraarticular adhesion), including 32 elbows in 32 patients. Arthroscopic elbow release was performed under general anesthesia. For intrinsic stiffness, a radiofrequency device was applied to release intraarticular scar tissue and create work space, which was rarely necessary in groups 1 and 2. In the postoperative period, X‐rays and CT scans were assessed at follow up to determine if there was HO formation, which was diagnosed when new calcifications were identified. The functional recovery was evaluated by comparing the range of motion (ROM) and pain relief preoperativley and postoperatively in each group. Other complications were also assessed postoperatively. Results: The patients' mean age was 38.6 years (range, 12–66), with 57 males and 41 females. Mean follow‐up was 21 months (range, 4–56). The active ROM and Mayo elbow performance index (MEPS) were improved from 93° ± 8.3° to 126° ± 12.4° ( P < 0.05) and 71.4 ± 7.6 to 91.3 ± 8.7 ( P < 0.001) in group 1, 66° ± 10.3° to 121° ± 10.7° ( P < 0.005) and 65.6 ± 9.2 to 93.5 ± 11.2 ( P < 0.05) in group 2, and 46° ± 6.7° to 91° ± 11.1° ( P < 0.001) and 52.3 ± 6.4 to 80.6 ± 9.4 ( P < 0.005) in group 3. HO developed in 25/101 cases (25%) and 4 patients with severe cases underwent repeat surgery. Those in group 1 were primarily arthritis patients; there were 3 out 46 cases with minor HO evident on X‐ray. In group 2, 1/23 had minor HO. In group 3, 21/32 patients had HO; 4 cases were considered severe, 4 were considered moderate, and 13 were considered minor. The average flexion–extension arc was improved by 47° at the last follow up. Other postoperative complications included 8 cases of prolonged drainage from portal sites, 17 transient nerve palsies, 1 permanent radial nerve injury, and 1 patient who developed delayed‐onset ulnar neuritis. This patient was fully recovered 5 months after surgery. Conclusions: The high incidence of HO formation after arthroscopic elbow release may relate to improper application of a radiofrequency device. Minimizing thermal injury from these radiofrequency devices could reduce HO formation and improve postoperative functional recovery. Abstract : The occurrence of heterotopic ossification(HO) after arthroscopic elbow release is unexpectedly high in our practice. Suspicious risk factors relate to these HO formation was investigated in this study.